Faktor-Faktor yang Mempengaruhi Kekurangan Pemahaman Masyarakat pada Asuransi Syariah di Kota Binjai - Feri Prayogi; Yusrizal Yusrizal (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study aims to determine the factors that traumatize people from insurance products in the city of Binjai. This research method uses an approach, namely a qualitative approach. The results of this study indicate that in creating people's interest in PT. Asuransi Prudential Syariah, there are triggering things that indoctrinate people's desire for Islamic insurance goods at the start of goods sold to users or the people. Then the invitation made by the agency from PT Asuransi Prudential Syariah to people who already know and use insurance services or who don't understand what insurance is, after that the people's income has no doctrine when the people become prudential sharia customers because the premium payment nominal can be adjusted to the nominal entry of prospective customers/customers. Keywords: Insurance, Society, and Products